PHANGS-JWST first results: stellar-feedback-driven excitation and dissociation of molecular gas in the starburst ring of NGC 1365? - Liu, Daizhong; Schinnerer, Eva; Kruijssen, Diederik; Chevance, Mélanie; Glover, Simon; Sormani, Mattia C.; Krieger, Sophia K.; Bigiel, Frank; Watkins, Elizabeth J.; Klessen, Ralf S.; Egorov, Oleg (The astrophysical journal. Part 2, Letters, 2023)
We compare embedded young massive star clusters (YMCs) to (sub-)millimeter line observations tracing the excitation and dissociation of molecular gas in the starburst ring of NGC 1365. This galaxy hosts one of the strongest nuclear starbursts and richest populations of YMCs within 20 Mpc. Here we combine near-/mid-IR PHANGS-JWST imaging with new Atacama Large Millimeter/submillimeter Array multi-J CO (1-0, 2-1 and 4-3) and [C i] (1-0) mapping, which we use to trace CO excitation via R 42 = I CO(4−3)/I CO(2−1) and R 21 = I CO(2−1)/I CO(1−0) and dissociation via R CICO = I [CI](1−0)/I CO(2−1) at 330 pc resolution. ...
Gesehen am 06.12.2023